Ethics and Legal Aspect of Termination of Pregnancy with Trisomy 13 (Patau Syndrome) - Dian Andriani Ratna Dewi; Febriansyah Darus; Hayra Diah Avianggi; Gunawan Rusuldi; Sutan Finekri Arifin Abidin (Green Publisher Indonesia, 2023)
Trisomy 13 is a serious genetic anomaly in the fetus that is one of the causes of abortion as a result of the chromosomal aneuploidy. Trisomy 13 affects roughly 1 in 10,000 to 20,000 live births, and more than 95% of pregnancies end in prenatal death. Due to the higher prevalence of preeclampsia and the danger of maternal death associated with early birth, abnormalities in these infants also have an impact on the mother's health. According to Law No. 36 of 2009 concerning Health, women who eligble for abortions if there are medical reasons to do so. The problems in this paper are 1) What are the ethical problems found in pregnancies with a fetus diagnosed with a genetic disorder due to trisomy 13? 2) What is the procedure for implementing medical abortion provocation that fulfills ethical aspects and complies with applicable regulations. To answer these problems, a research using normative legal research, accompanied by reports of cases of abortion. This normative legal research focuses on ethical and legal aspects of the implementation of provocative medical abortion following statutory regulations. This normative legal research starts with articles and case reports of fetal pregnancies with genetic disorders from the Gatot Soebroto Army Hospital. The results of the study show that consent to termination of pregnancy with medical indications by the patient and approved by the husband/family. T